Working group Report on Sericulture 1964 - Ministry of Commerce (Ministry of Commerce, Government of India, 1964)
The 1964 Working Group Report on Sericulture provides a comprehensive evaluation of India’s silk industry, addressing production, employment, exports, and research during the Third and Fourth Five-Year Plans. India, producing all four types of natural silk, faced challenges in productivity, cooperative development, and quality control. The report emphasizes enhancing rural employment, improving silk quality, and fostering research through institutions like the Central Sericultural Research Institute. It highlights the significance of handloom weaving centers, particularly in Varanasi and West Bengal, and the role of cooperatives and export promotion schemes to stabilize markets. Financial allocations and structured assistance programs are recommended to improve training, infrastructure, and institutional support. Strategic initiatives, including modernized rearing techniques, training of technical personnel, and targeted export incentives, aim to strengthen India’s position in the global silk market while ensuring sustainable growth and economic benefits for rural communities.
Ministry of Commerce, Government of India
Keywords: Sericulture; Silk Production; Handloom Weaving; Cooperative Societies; Export Assistance; Research and Training; Mulberry Silk; Tasar Silk; Financial Allocation; Rural Employment; Central Silk Board; Quality Improvement